Cathedral Square: the historic heart of Perth - Whish-Wilson, David (Treasury WA Pty Ltd & Fremantle Press, 2019)
This book is a work of creative non-fiction and a social history of the Cathedral Square precinct that focusses on the history, people, art and architecture of a single city block. Text, with photographs, maps, designs.